A PAPR Reduction Method Based on the CT Codes. Issue 5 (February 2020) - Deng, Zaihui; Ding, Sha
Abstract: This paper proposes a Peak-to-Average Power Ratio (PAPR) reduction method based on the Chinese Transform (CT) codes intended for the Orthogonal Frequency Division Multiplexing (OFDM) systems. Based on the advantage that remainder is smaller than the corresponding modulus during the CT encoding, the proposed method adopts the strategy of dynamical controlling the dynamic range of the OFDM transmission signal at the front stage. The simulation results show that the proposed method is effective in reducing the PAPR of OFDM system.